Interfirm partnerships and organizational innovation: Study of SMEs in the automotive sector - Mário Franco; Heiko Haase (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This study aims to analyze the influence that interfirm partnership motives can have on the implementation of organizational innovation activities. To achieve this aim, a quantitative cross-sectional research design was adopted, surveying owners-managers of small and medium-sized enterprises in the automotive sector. Based on the empirical evidence, the study concludes that the motives for partnership formation are related to organizational innovation activities, but only partially. Of the four main factors for establishing interfirm partnerships ("Efficiency", "Innovation and learning", "Market opportunities", "Technology and competition"), only the motives associated with the latter were shown to have a positive and significant influence on organizational innovation. Implications for theory and practice are also presented.
Keywords: 650; open innovation; automotive sector; interfirm partnerships; organizational innovation; SMEs; technology